Difunctionalization of alkenes with iodine and tert-butyl hydroperoxide (TBHP) at room temperature for the synthesis of 1-(tert-butylperoxy)-2-iodoethanes - Wang, Hao; Chen, Cui; Liu, Weibing; Zhu, Zhibo (Beilstein Journal of Organic Chemistry, 2017)
We developed a direct vicinal difunctionalization of alkenes with iodine and TBHP at room temperature. This iodination and peroxidation in a one-pot synthesis produces 1-(tert-butylperoxy)-2-iodoethanes, which are inaccessible through conventional synthetic methods. This method generates multiple radical intermediates in situ and has excellent regioselectivity, a broad substrate scope and mild conditions. The iodine and peroxide groups of 1-(tert-butylperoxy)-2-iodoethanes have several potential applications and allow further chemical modifications, enabling the preparation of synthetically valuable molecules.
Keywords: difunctionalization of alkenesiodine; iodination–peroxidation reaction; TBHP